Success factors for urban brownfield redevelopments in South Africa - Goosen, Johan Jacobus (My University, 2017)
This research sought to identify the key success factors associated with industrial brownfields site redevelopment projects in urban areas of South Africa. Nine such success factors were identified from international and local literature. Through documentary research, three brownfield case studies in Johannesburg were investigated. These included the Newtown Cultural Precinct, the Egoli Gas site and the AECI Modderfontein site. Commonalities includes location within the urban edge, original industrial land use, and the redevelopment intent of the landowners. Aspects differing among the sites include distance from the inner city, size, the certainty of contamination and redevelopment success. Based on the findings of the three case studies, the nine success factors were refined. The factors are no or low contamination, brownfields policy maturity, certainty regarding liability for remediation, risk-based land use options, favourable market conditions, quick funding access with rapid statutory approvals, readily available municipal services and transport infrastructure, and strong political and community support. The case study findings provide indications towards generalisation for success factors that may apply to future brownfields projects. Further research required includes a larger database of brownfields redevelopment case studies to be developed for South African, in order to further test associated success factors.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, Johannesburg 2017
Keywords: Urban renewal--South Africa; Brownfields--South Africa; Hazardous waste site remediation--South Africa